Network Determinants of Cross-Border Merger and Acquisition Decisions - Didier, Tatiana (IMF Working Papers; Working Paper, 2019)
This paper assesses whether cross-border M and A decisions exhibit network effects. We estimate exponential random graph models (ERGM) and temporal exponential random graph models (TERGM) to evaluate the determinants of cross-country M and A investments at the sectoral level. The results show that transitivity matters: a country is more likely to invest in a new destination if one of its existing partners has already made some investments there. In line with the literature on export platforms and informational barriers, we find a sizable impact of third country effects on the creation of new investments. This effect is sizable and larger than some of the more traditional M and A determinants, such as trade openness.